2019
DOI: 10.1038/s41598-019-50411-w
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-fast direct growth of metallic micro- and nano-structures by focused ion beam irradiation

Abstract: An ultra-fast method to directly grow metallic micro- and nano-structures is introduced. It relies on a Focused Ion Beam (FIB) and a condensed layer of suitable precursor material formed on the substrate under cryogenic conditions. The technique implies cooling the substrate below the condensation temperature of the gaseous precursor material, subsequently irradiating with ions according to the wanted pattern, and posteriorly heating the substrate above the condensation temperature. Here, using W(CO)6 as the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 48 publications
0
42
1
Order By: Relevance
“…In the current work, the simulated tungsten concentration of about 8% at a fluence of 4 × 10 14 ions/cm 2 ( Figure 5), which is in the range of the optimized irradiation dose according to Córdoba et al [55], is also lower than the experimental surface concentration of above 20%, which gives an indication that diffusion processes and/or outgassing after the dissociation of the precursor molecules play a role but are not accounted for in the modelling. Although the W surface concentration starts to increase in the simulations with a fluence of 4 × 10 14 ions/cm 2 (Figure 5b), the tungsten surface concentration only starts to be significantly above the initial concentration of the precursor film for fluences above 10 16 ions/cm 2 (see Figure A1 in Appendix A).…”
Section: W-c Deposits Grown By Cryo-fibidcontrasting
confidence: 59%
See 3 more Smart Citations
“…In the current work, the simulated tungsten concentration of about 8% at a fluence of 4 × 10 14 ions/cm 2 ( Figure 5), which is in the range of the optimized irradiation dose according to Córdoba et al [55], is also lower than the experimental surface concentration of above 20%, which gives an indication that diffusion processes and/or outgassing after the dissociation of the precursor molecules play a role but are not accounted for in the modelling. Although the W surface concentration starts to increase in the simulations with a fluence of 4 × 10 14 ions/cm 2 (Figure 5b), the tungsten surface concentration only starts to be significantly above the initial concentration of the precursor film for fluences above 10 16 ions/cm 2 (see Figure A1 in Appendix A).…”
Section: W-c Deposits Grown By Cryo-fibidcontrasting
confidence: 59%
“…However, no particular application was discussed or targeted. [55]. As shown in Figure 4, such working conditions plus ion doses in the range of 50 μC/cm 2 have been found favorable for obtaining homogeneous void-free W-C deposits.…”
Section: W-c Deposits Grown By Cryo-fibidmentioning
confidence: 76%
See 2 more Smart Citations
“…Several recent studies have demonstrated that focused electron beam induced processing (FEBIP) has high potential for the controlled bottom-up fabrication of metallic 3D nanostructures [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Furthermore, the basic processes during FEBIP are understood to more and more detail leading to developments towards more diverse, cleaner and more defined deposits for various potential applications [7,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%